2019
DOI: 10.24171/j.phrp.2019.10.5.06
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Deprivation and Unmet Health Care Needs: A Multilevel Analysis of Older Individuals in South Korea

Abstract: ObjectivesIn this study the relationship between neighborhood deprivation and the unmet health care needs of elderly individuals (≥ 65 years) was examined. Some previous studies suggested that neighborhood characteristics affect access to health care, yet research on the unmet needs of older individuals is limited.MethodsMultilevel logistic regression analysis was used to assess the relationship of neighborhood-level factors with unmet health care needs due to costs, adjusting for individual-level factors, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…When considering the population structure in rural areas and the poverty rate of the elderly population in Korea, individuals with low absolute income are likely to experience higher economic stress in urban areas than in rural areas, and may therefore have a higher risk of depression. 38 39 …”
Section: Discussionmentioning
confidence: 99%
“…When considering the population structure in rural areas and the poverty rate of the elderly population in Korea, individuals with low absolute income are likely to experience higher economic stress in urban areas than in rural areas, and may therefore have a higher risk of depression. 38 39 …”
Section: Discussionmentioning
confidence: 99%
“…Especially in Korea, many low-income oldest-old adults report inadequate access to their needed healthcare because of skyrocketing healthcare costs, limited noninsured services, and substantial out-of-pocket payments 48 . Furthermore, they have not benefitted from the equitable utilization of primary care and medical services as Korean society increasingly suffers residential segregation based on SEP 49 . According to previous evidence and the current findings, it is essential to implement targeted interventions or policies to improve access to healthcare in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Individualistic values have become stronger among South Korean people, which may disrupt neighbourhood processes and undermine social connections among residents (Lee, 2021). These weakened community ties and cohesion may be negatively associated with both parents' mental health and interactions with their children (Jang et al, 2009;Lee et al, 2019;Oh et al, 2013). Indeed, previous studies have suggested that these cultural contexts may partly explain why South Korea has the highest prevalence of depression and death by suicide among Organization for Economic Cooperation and Development (OECD) countries (Kim & Park, 2021;OECD, 2021;Yim & Kwon, 2021).…”
Section: Gunnmentioning
confidence: 99%